Additive manufacturing of 3D porous alkali-free bioactive glass scaffolds for healthcare applications - Marzi, Anna de (2019)
Tissue Engineering is a multidisciplinary field of study based on the techniques, methods and knowledge of biology, medicine and engineering. The aim is to produce artificial devices able to act as temporary substitutes of damaged tissues: the structure realized must serve as supports for cell attachment and proliferation as well as the production of extracellular matrix, ideally until the same device degrades. The great issues related to this approach are therefore implementing a suitable scaffold material produced with an adequate technique in order to satisfy the above requirements. In this Thesis project, an alkali-free bioactive glass composition in the binary system of Diopside-Tricalcium Phosphate that has already shown promising properties for tissue engineering and bone regeneration was selected. The robocasting technique was adopted for manufacturing 3D porous scaffolds with adequate structures and porosities designed by CAD. The work included different steps such as: (i) preparation and characterization of glass powders with different particle size distributions to enhance the packing ability; (ii) preparation of concentrated suspensions and investigate the dependence of their rheological properties on solid loading and the content of CMC selected as the single processing additive; (iii) production of the scaffold with different porosity; (iv) characterization of the printed structures before and after sintering process. The results obtained demonstrated that a 1:1 mixture of glass powders having mean particle diameters of 1 m and 45 m enables preparing suitable suspensions by playing with the contents of CMC and solid loading. The printed scaffolds present well-defined geometry and good shape retention. The work carried out could be considered as a very promising starting point for further studies aiming at obtaining further improvements